2015
DOI: 10.7732/kjpr.2015.28.2.253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wet Cold and Gibberellin Treatments on Germination of Dwarf Stone Pine Seeds

Abstract: -In South Korea, Pinus pumila (Pall.) Regel (dwarf stone pine) has been designated as a critically endangered species by the Korea Forest Service. We have difficulties in obtaining the seeds of P. pumila because P. pumila grows only in the Daecheongbong area (1550-1700 m above sea level) of Mt. Seorak and almost all of its cones are damaged by birds and rodents. For establishing an ex situ conservation stand of P. pumila, this study was conducted to figure out the effects of wet cold (cold stratification, prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…were enhanced by GA 3 treatment to 71.3%, 87.2%, and 91.7% at GA 3 concentrations of 50, 100, and 1000 mg/L, respectively, compared with that of the control (44.7%) (Song et al 2019b). Zanthoxylum piperitum (Kim et al 1997), Exochorda serratifolia , Pinus pumila (Lim et al 2015), Lychnis wilfordii (Regel) Maxim (Ryu et al 2017), and many other species have also been shown to have improved germination percentages following gibberellin treatment, suggesting that this treatment breaks the PD of seeds. Accordingly, these findings showed that the concentration and time of gibberellin treatment were critical factors for improving germination percentages.…”
Section: Discussionmentioning
confidence: 99%
“…were enhanced by GA 3 treatment to 71.3%, 87.2%, and 91.7% at GA 3 concentrations of 50, 100, and 1000 mg/L, respectively, compared with that of the control (44.7%) (Song et al 2019b). Zanthoxylum piperitum (Kim et al 1997), Exochorda serratifolia , Pinus pumila (Lim et al 2015), Lychnis wilfordii (Regel) Maxim (Ryu et al 2017), and many other species have also been shown to have improved germination percentages following gibberellin treatment, suggesting that this treatment breaks the PD of seeds. Accordingly, these findings showed that the concentration and time of gibberellin treatment were critical factors for improving germination percentages.…”
Section: Discussionmentioning
confidence: 99%
“…The germination rates of Korean perilla seeds under PEG priming treatment increased compared to the controls, as was previously reported for germination rates and germinative power of Alnus sibirica (Park et al 2013). In the case of Zanthoxylum piperitum seeds, GA 3 has been reported to increase the germination rate with increasing immersion time and concentration (Lim et al 2015). The germination rate was significantly improved with GA 3 levels of 25 ppm, and the germination rate tended to increase with increasing GA 3 concentrations in Lithospermum erythrorhizon seed (Kim et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…는 종에 따라 종자의 휴면을 타파하기 위한 GA의 적정 농도가 각각 다르다고 하였으며, 딸기나무(Arbutus unedo L.)의 경우 300mg•L -1 GA3처리 시 광의 유무와 관계없이 휴면을 타파하였으나(Tilki, 2004), 눈잣나무[Pinus pumila (Pall.) Regel]의 경우 GA3를 0, 100, 500, 1000mg•L -1 농도로 처리하였을 때, 각각 48.0, 79.0, 75.7, 65.8%의 발아율을 나타내었다(Lim et al, 2015). PD는 휴면의 깊이에 따라 세 가지(non-deep, intermediate, deep PD)로 나눌 수 있다(Baskin and Baskin, 2014).…”
unclassified